The Validity and Evidentiary Strength of Foreign Electronic Signatures in Cross-Border Digital Transactions in Indonesia - Halena Artamevia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid growth of cross-border digital transactions has positioned electronic signatures as a fundamental tool for ensuring the legal validity of documents. However, the recognition of foreign electronic signatures within the Indonesian legal system remains a complex issue, particularly in relation to legal validity, evidentiary value, and differences in regulatory standards across jurisdictions. This study aims to analyze the validity and evidentiary strength of foreign electronic signatures under Indonesian law, as well as their conformity with international principles reflected in the UNCITRAL Model Law on Electronic Signatures 2001. This research employs a normative legal method using statutory and conceptual approaches. The findings indicate that, in principle, foreign electronic signatures can be legally recognized as long as they meet reliability and security standards. Nevertheless, in practice, their evidentiary value is not equivalent to domestically certified electronic signatures. Regulatory requirements, including system integration and compliance with national administrative standards, create significant barriers for foreign providers. These conditions lead to increased burdens of proof in dispute resolution and hinder legal interoperability in cross-border transactions. Therefore, there is a need to strengthen mutual recognition mechanisms and enhance international cooperation to balance digital sovereignty with global transaction efficiency.